Dall’Etiopia al Medio Oriente. Pratiche, retoriche e discorsi sulle esperienze delle lavoratrici domestiche etiopi - Cirillo, Silvia (Antropologia Pubblica, 2024)
Drawing on field research conducted in Ethiopia in 2018 and 2019, this contribution reflects on the ambiguities and contradictions of the discourses and practices promoted by the Ethiopian government and national and international organisations on the topic of women’s domestic work. On the one hand, there is a constant focus on the exploitative experiences of female workers abroad (particularly in the Middle East), with the simplistic distinction between migration routes defined as “safe” or “dangerous”, “legal” or “illegal”. On the other hand, there is an absence of debate on the experiences of domestic workers in Ethiopia. This scenario emerges from the analysis of the evolution of Ethiopian migration policies over the last two decades and from the testimonies of female domestic workers. The specific case of Saudi Arabia will be illustrated at the conclusion of the article, in order to better understand the sense of “confusion” described by many women as a consequence of the ambiguous changeability of migration policies.